Six2 promotes non–small cell lung cancer cell stemness via transcriptionally and epigenetically regulating E‐cadherin. (22nd April 2019) - Hou, Huaying; Yu, Xiaoming; Cong, Ping; Zhou, Yong; Xu, Ying; Jiang, Yuhua
Abstract: Objectives: The roles and related mechanisms of six2 in regulating non–small cell lung cancer (NSCLC) cells progression are unclear. This work aimed to explore the roles of six2 in NSCLC cell stemness. Materials and Methods: Kaplan‐Meier plotter analysis was used to examine the correlation between six2 expression and the survival of NSCLC patients. Quantitative reverse transcription PCR and Western blot were performed to detect six2 expression in clinical samples. Moreover, transwell migration, tumour spheroid formation and in vivo tumour formation assays were used to examine the effects of six2 on NSCLC cell progression. Additionally, methylation analysis was carried out to measure E‐cadherin methylation level in different cells. Finally, cell viability assay was performed to explore the effects of six2 on chemotherapeutic sensitivity of NSCLC cells. Results: Lung cancer patients with a higher six2 expression level displayed a shorter overall survival. Six2 expression was higher in lung cancer tissues than in normal adjacent tissues. Additionally, six2 knockdown suppressed NSCLC cell stemness. Mechanistically, six2 overexpression inhibited epithelial marker E‐cadherin expression via stimulating its promoter methylation. And E‐cadherin knockdown rescued six2 knockdown‐induced decrease of NSCLC cancer cell stemness. Notably, six2 knockdown enhanced cisplatin sensitivity in parental NSCLC cells and attenuated cisplatin resistance in cisplatin‐resistant NSCLC cells. Conclusions: Our results suggest that six2 facilitates NSCLC cell stemness and attenuates chemotherapeutic sensitivity via suppressing E‐cadherin expression.